2012
DOI: 10.1094/mpmi-09-11-0232
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Regulates Basal Resistance to Fusarium Head Blight in Wheat

Abstract: Fusarium head blight (FHB) is a destructive disease of cereal crops such as wheat and barley. Previously, expression in wheat of the Arabidopsis NPR1 gene (AtNPR1), which encodes a key regulator of salicylic acid (SA) signaling, was shown to reduce severity of FHB caused by Fusarium graminearum. It was hypothesized that SA signaling contributes to wheat defense against F. graminearum. Here, we show that increased accumulation of SA in fungusinfected spikes correlated with elevated expression of the SA-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 68 publications
(110 reference statements)
4
137
1
7
Order By: Relevance
“…albedinis (Foa) was confirmed by Dihazi et al (2011). even though, a few other studies also have reported that exogenous application of salicylic acid induces pathogenesis-related protein-1 and helps in defense response, however, recent studies have reported that internally SA loses its prominent role as a resistance response against necrotrophic pathogens like Fox but induces an effective defense response against biotrophic pathogens (edgar et al 2006;Li et al 2012;Makandar et al 2012).…”
Section: Salicylic Acid (Sa) Jasmonic Acid (Ja) and Ethylene (Et)mentioning
confidence: 93%
See 1 more Smart Citation
“…albedinis (Foa) was confirmed by Dihazi et al (2011). even though, a few other studies also have reported that exogenous application of salicylic acid induces pathogenesis-related protein-1 and helps in defense response, however, recent studies have reported that internally SA loses its prominent role as a resistance response against necrotrophic pathogens like Fox but induces an effective defense response against biotrophic pathogens (edgar et al 2006;Li et al 2012;Makandar et al 2012).…”
Section: Salicylic Acid (Sa) Jasmonic Acid (Ja) and Ethylene (Et)mentioning
confidence: 93%
“…JA signaling has a dichotomous involvement in the Arabidopsis interaction with F. graminearum, contributing to the attenuation of SA signaling during the early stages of infection and promotion of defense against F. graminearum during later stages of infection (Makandar et al 2010). Similarly in another study involving Arabidopsis, a complex interaction between SA/NPR1 and JA signaling regulates basal resistance against Fusarium head blight (FHB), because exposure to MeJA vapors either prior to fungal inoculation or during the early stages of fungal infection attenuated AtNPR1-conferred FHB resistance suggesting that during the early stages of infection, JA signaling attenuates SA/NPR1-determined defense signaling (Makandar et al 2012). These findings were proved against hemibiotrophic pathogen F. graminearum.…”
Section: Salicylic Acid (Sa) Jasmonic Acid (Ja) and Ethylene (Et)mentioning
confidence: 97%
“…Additionally, we selected different plant defense genes encoding pathogenesis-related proteins, which are known to play a role in the defense against infection with F. graminearum, namely, the pathogenesis-related proteins PR1 (Makandar et al, 2012), PR2, b-1,3-glucanase (Gao et al, 2013), PR4, shown to possess antifungal properties against Fusarium spp. (Bertini et al, 2009), and PR5 (thaumatinlike protein; Gao et al, 2013).…”
Section: Gene Expression Of Preexposed Seedlings After Treatment Withmentioning
confidence: 99%
“…The resistance of wheat against infection by F. graminearum has primarily been attributed to SA-mediated (Makandar et al, 2012) and JA-mediated (Li and Yen, 2008;Qi et al, 2012) defense pathways. Because of the hemibiotrophic lifestyle of F. graminearum, it can be expected that SA and JA will play a sequential role in the plant defense against F. graminearum.…”
Section: Don Analysismentioning
confidence: 99%
“…SA mutants impaired in the SA signalling have shown susceptibility to this pathogen; on the other hand, SA applications increased resistance to F. graminearum. Moreover, JA signalling contributes to F. graminearum susceptibility by SA signalling attenuation during the initial infection but promoting resistance as the disease progresses (Makandar et al 2010(Makandar et al , 2012. Not only SA inhibits the F. graminearum growth in acidic conditions but also this pathogen has the ability to metabolize SA to SA biosynthesis intermediates such as catechol in basic growth conditions.…”
Section: Fusarium Species Studiesmentioning
confidence: 99%